2014
DOI: 10.1017/s1049023x14000284
|View full text |Cite
|
Sign up to set email alerts
|

Dextrose 10% in the Treatment of Out-of-Hospital Hypoglycemia

Abstract: In addition to practical reasons of cost and availability, theoretical risks of using 50 mL of D50 in the out-of-hospital setting include extravasation injury, direct toxic effects of hypertonic dextrose, and potential neurotoxic effects of hyperglycemia. The results of one local EMS system over an 18-week period demonstrate the feasibility, safety, and efficacy of using 100 mL of D10 as an alternative. Additionally, the linear regression line of repeat glucose measurements suggests that there may be little or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
1
11
0
1
Order By: Relevance
“…Many studies have demonstrated the feasibility, safety, and efficacy of using D10 instead of D50, with no increased time to resolution of symptoms and no significant differences in on-scene times. 70 , 71 In comparing glucagon intramuscular (IM) to dextrose intravenous (IV), median time to full orientation for glucagon was 10–30 minutes, compared with 1–10 minutes for dextrose. 72 , 73 …”
Section: Methodsmentioning
confidence: 99%
“…Many studies have demonstrated the feasibility, safety, and efficacy of using D10 instead of D50, with no increased time to resolution of symptoms and no significant differences in on-scene times. 70 , 71 In comparing glucagon intramuscular (IM) to dextrose intravenous (IV), median time to full orientation for glucagon was 10–30 minutes, compared with 1–10 minutes for dextrose. 72 , 73 …”
Section: Methodsmentioning
confidence: 99%
“…No difference in time to restoration of consciousness was found between the treatment groups (median: 8 min), but total dextrose administered and post‐treatment glucose level were greater in the 50% dextrose‐treated cohort, leading authors to recommend the 10% preparation. An observational study evaluated the efficacy of 10% dextrose in the prehospital environment and showed that the administration of 10 g of 10% dextrose was effective in restoring euglycaemia in the majority (78%) of participants, with a further 17.7% responding after a second dose (20 g total). No timing intervals were imposed or examined in that study, however, and no other studies comparing treatment dosage or repeat treatment intervals of i.v.…”
Section: Resultsmentioning
confidence: 99%
“…Effective dosages of i.v. dextrose range from 10 to 25 g and, while both 50% and 10% concentrations restore consciousness, the 10% preparation has been advocated because of lower post‐treatment glycaemia and less total glucose administration . Although i.m.…”
Section: Discussionmentioning
confidence: 99%
“…This case emphasizes the importance of early detection and treatment when suspecting extravasation of D50 in order to prevent the development of serious complications like compartment syndrome. 10% dextrose (D10) is now emerging as a safer (given the lower concentration) and equally effective alternative to D50 administration and could become the standard of care for hypoglycemia management [3].…”
Section: Discussionmentioning
confidence: 99%